Validation of the 10/66 Dementia Research Group Diagnostic Assessment for Dementia in Arabic: A Study in Lebanon. (December 2014) - Phung, Kieu T. T.; Chaaya, Monique; Waldemar, Gunhild; Atweh, Samir; Asmar, Khalil; Ghusn, Husam; Karam, Georges; Sawaya, Raja; Khoury, Rose Mary; Zeinaty, Ibrahim; Salman, Sandrine; Hammoud, Salem; et al.
Objectives: In the North Africa and Middle East region, the illiteracy rates among older people are high, posing a great challenge to cognitive assessment. Validated diagnostic instruments for dementia in Arabic are lacking, hampering the development of dementia research in the region. The study aimed at validating the Arabic version of the 10/66 Dementia Research Group (DRG) diagnostic assessment for dementia to determine whether it is suitable for case ascertainment in epidemiological research. Methods: A total of 244 participants older than 65 years were included, 100 with normal cognition and 144 with mild to moderate dementia. Dementia was diagnosed by clinicians according to Diagnostic and Statistical Manual of Mental Disorders (Fourth Edition) criteria. Depression was diagnosed using the Geriatric Mental State. Trained interviewers blind to the cognitive status of the participants administered the 10/66 DRG diagnostic assessment to the participants and interviewed the caregivers. The discriminatory ability of the 10/66 DRG assessment and its subcomponents were evaluated against the clinical diagnoses. Results: Half of the participants had no formal education and 49% of them were depressed. The 10/66 DRG diagnostic assessment showed excellent sensitivity (92.0%), specificity (95.1%), positive predictive value (PPV, 92.9%), and low false-positive rates among controls with no formal education (8.1%) and depression (5.6%). Each subcomponent of the 10/66 DRG diagnostic assessment independently predicted dementia diagnosis. The predictive ability of the 10/66 DRG assessment was superior to that of its subcomponents. Conclusion: The 10/66 DRG diagnostic assessment for dementia is well suited for case ascertainment in epidemiological studies among Arabic-speaking older population with high prevalence of illiteracy.